ChemInform Abstract: Isolation, Structure Determination and Cytotoxicity Studies of Tryptophan Alkaloids from an Australian Marine Sponge Hyrtios sp. Issue 6 (February 2015) - Khokhar, Shahan; Feng, Yunjiang; Campitelli, Marc R.; Ekins, Merrick G.; Hooper, John N. A.; Beattie, Karren D.; Sadowski, Martin C.; Nelson, Colleen C.; Davis, Rohan A.
Abstract Two new tryptophan alkaloids, 6‐oxofascaplysin (I) and secofascaplysic acid (II), are isolated together with the known metabolites fascaplysin and reticulatate.